I-It, I-Thou, I-Robot: The Perceived Humanness of AI in Human-Machine Communication. Issue 3 (26th May 2020) - Westerman, David; Edwards, Autumn P.; Edwards, Chad; Luo, Zhenyang; Spence, Patric R.
ABSTRACT: As artificial intelligence (AI) technologies become more common and capable interaction partners (human-machine communication; HMC), understanding how people perceive and interact with them becomes increasingly important to study. This essay argues that one important avenue for this study is the application of relevant interpersonal and computer-mediated communication (CMC) theories. The paper suggests that these theories are relevant because the Computers as Social Actors (CASA) approach has shown that people tend to respond to technologies as they do to other people. It summarizes some theories that may be especially useful for future study in this field. Finally, a case is made that the study of AI and HMC may also be important for greater understanding of the human-human communication process as well.